Revised Second Five Year Plan (1956-57 to 1960-61) Jammu and Kashmir State - Planning Commission (Planning Commission, 1956)
The provision under backward classes has been increased from 30 lakhs to 41 with consequent reduction in the providing for Social Welfare from 20 to 9 as recommended by the Working Group. This was inescapable since the problems of backward classes have not been tackled so far effectively. the inadequate size of the allocation under this head was realised by the Working Group who were of the opinion that those ceilings could be revised in due course, other changes are minor.
Jammu and Kashmir State